"Let Me Do What I Please With It . . . Don't Decide My Identity For Me": LGBTQ+ Youth Experiences of Social Media in Narrative Identity Development. Issue 1 (January 2020) - Bates, Adam; Hobman, Trish; Bell, Beth T.
Social media provides Lesbian Gay Bisexual Transgender Queer Plus (LGBTQ+) youth with daily access to a broader sociocultural dialogue that may shape narrative identity development. Through in-depth narrative interviews, this study sought to understand the lived experiences of 11 LGBTQ+ undergraduates ( age range = 19-23) building narrative identities in the cultural context of social media and the role of social media within this process. Interviews were analyzed using an interpretative, individual analysis of personal stories. These experiences were then compared and contrasted through thematic analysis to identify four shared narrative themes. Narratives of merging safe spaces highlight how LGBTQ+ youth now have regular access to safe environments online/offline which facilitate more secure identity development. Narratives of external identity alignment describe social media as a tool for LGBTQ+ youth to seek out identities that match their preexisting sense of self. Narratives of multiple context-based identities encapsulate how adolescents' identity markers are multiple and invoked in a context-dependent manner. Finally, narratives of individuality and autonomy characterize how LGBTQ+ youth perceive themselves as highly individualized members of a wider community. These findings highlight the complex role social media plays within LGBTQ+ youth identity development. The implications are discussed within.